Influencing factors on green supply chain resilience of agricultural products: an improved gray-DEMATEL-ISM approach - Wang, Jing; Liu, Mingfei; Chen, Yun; Yu, Mengyun (Frontiers in Sustainable Food Systems, 2023)
Natural disasters and the COVID-19 epidemic have caused serious consequences such as long-term disruption and chain reaction to the global supply chain. Global warming caused by a large number of greenhouse gases has accelerated the attention of society to environmental sustainability.Therefore, identifying the transmission path of the factors that affect the green supply chain resilience of agricultural products is the primary task to accelerate the construction of a modern circulation system of agricultural products, ensure market supply and protect the environment. Based on the stakeholder theory, this study uses the literature research method to identify 15 factors that affect the green supply chain resilience of agricultural products. Through improving DEMATEL and ISM to study the internal relationship between the influencing factors, build a multi-level hierarchical structure model, and identify the basic transmission process and path of the influencing factors. The results show that the government's issuance of environmental policies and the provision of financial subsidies are important driving forces to strengthen the green supply chain resilience of agricultural products; The collaboration capability and business sustainability goals directly affect the green supply chain resilience of agricultural products; Agility, digital infrastructure construction, sustainability beliefs of top managers, public opinion with environment information disclosure and other factors indirectly affect the green supply chain resilience of agricultural products. The conclusion shows that the most important way to guide the green supply chain of agricultural products to develop towards standardization, normalization and sustainability is to guide the organization to set business sustainable goals and strengthen the collaborative cooperation ability of all stakeholders in the supply chain, with the government issuing environmental policies and providing financial subsidies as the driving factors. This study can provide theoretical basis for the government and enterprises to strengthen the green supply chain resilience of agricultural products.